2008
DOI: 10.1111/j.1532-950x.2008.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Biomechanical Comparison of a 5.5 mm Limited‐Contact Dynamic Compression Plate Fixation with a 4.5 mm Limited‐Contact Dynamic Compression Plate Fixation of Osteotomized Equine Third Metacarpal Bones

Abstract: The results of this in vitro study may provide information to aid in the selection of a biological plate for long bone fracture repair in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 6 publications
2
18
0
1
Order By: Relevance
“…The maximum load of 7.5 kN was chosen to be 50% of the mean yield load of the 4.5 mm broad limited‐contact dynamic compression plate‐MC3 construct in a pilot study, thus within the elastic region of the load deformation curve 9 . This maximum load of 7.5 kN was chosen in this study, as well as others studies, 6,7 to be consistent with an early study 8 . The number of cycles to failure was recorded, with failure defined as screw loosening, plastic deformation of implants, or catastrophic failure of implants, determined by a sudden decrease in load.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…The maximum load of 7.5 kN was chosen to be 50% of the mean yield load of the 4.5 mm broad limited‐contact dynamic compression plate‐MC3 construct in a pilot study, thus within the elastic region of the load deformation curve 9 . This maximum load of 7.5 kN was chosen in this study, as well as others studies, 6,7 to be consistent with an early study 8 . The number of cycles to failure was recorded, with failure defined as screw loosening, plastic deformation of implants, or catastrophic failure of implants, determined by a sudden decrease in load.…”
Section: Methodsmentioning
confidence: 84%
“…To maintain consistency with previous studies, 6,7 an 8‐hole 5.5 LCP was required; however, the 5.5 LCP is only available in 10 holes and greater. A 10‐hole 5.5 LCP was placed in a positioning jig and the first and the 10th holes were cut off using an abrasive cut‐off saw.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The results of a previous study 7 and the companion study 11 demonstrated that an important factor affecting the number of cycles to failure is the relative plate‐bone contact of the different constructs; however, there are other factors that contribute to the difference between the number of cycles to failure under palmarodorsal 4‐point bending, for the 2 fixation methods. Such factors include screw size, screw type, and pattern of screw placement used in securing the plate.…”
Section: Discussionmentioning
confidence: 98%
“…Das Akronym "PC-FIX" steht für "Point-Contact Fixateur", was eine Weiterentwicklung der LC-DCP darstellt und als eigentlicher "Fixateur Interne" angesehen werden kann (Tepic und Perren 1995 Zahlreiche In vitro-Studien konnten die Überlegenheit der Verriegelungssysteme über die früheren Frakturfixationstechniken beweisen (Sod et al 2008a, 2008b, Ahern et al 2013 (Bramlage 1999, Fürst 2012 …”
Section: Pc-fixunclassified